A novel approach to achieving a low Young's modulus in titanium-based metallic glasses. Issue 1 (15th February 2019) - Luo, Jia-Peng; Jia, Xiao; Zheng, Dong-Lai; Wang, Gang; Sun, Jian-Fei; Yan, Ming
Abstract : Titanium (Ti)-based materials are favourable for biomedical implant applications because of their unique biocompatibility, good corrosion resistance and moderate overall mechanical properties. Furthermore, amorphous titanium-based metallic glasses may take a decent share of the market as a result of their excellent properties. Developing low-modulus titanium-based metallic glasses is of both scientific and practical interests. In this study, the authors have analysed more than 40 different types of titanium-based metallic glasses and introduced two modified parameters that are based on a molecular orbital approach but are better in the prediction of the Young's modulus of metal implants, which should be about 30 MPa. Alloying elements are categorised and compared accordingly. Zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), tin (Sn) and molybdenum (Mo) are proposed to be effective in designing low-Young's-modulus biomedical titanium-based metallic glasses.